RESILIENSI KOLEKTIF LEMBAGA KEAGAMAAN KOMUNITAS DIFABEL - Ahmadi, Rizqa; Nafis, Muhammad Muntahibun; Restendy, Mochammad Sinung (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2023)
For some reason, the religious needs’ fulfillment of the diffable communities was not in line with the supply from both government and non-government institutions. This is inseparable from the impartiality of policies and low awareness, as well as a lack of public awareness of the rights of disabled communities. As a result, the negative stigma of being a non-productive community as well as ghair mukallaf (free of religious burdens) is still attached to them. The Taman Pendidikan al-Qur’an Spirit Da'wah Indonesia Foundation (TPQLB SPIDI) Tulungagung, which is the focus of this study, is one of the institutions that believe that their involvement is the answer to these needs, inequality, and slanted views. This institution survives and even continues to grow and steal the public's attention. This article is a record of community empowerment based on the Asset Based Community Development (ABCD) method with an emphasis on the analysis of organizational resilience in a sociological perspective. As a non-profit and non-governmental organization, TPQLB SPIDI can be resilient to several factors, such as mindful action, performance optimization, adaptive innovation, and paradoxical thinking. In addition, it is also supported by adequate social capital.